2016
DOI: 10.1111/jocn.13530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the application of manual pressure before the administration of intramuscular injections on students' perceptions of postinjection pain: a semi‐experimental study

Abstract: Applying pressure to the injection area is a simple and cost-effective method to reduce the pain associated with injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 17 publications
2
43
0
5
Order By: Relevance
“…Beside these, studies that suggest performing direct pressure to the injection site independent of acupressure points were also found to be effective for reducing injection pain (Derya et al, ; Nasiry et al, ; Öztürk et al, ). According to the study of Öztürk et al, after pressure was performed on the injection site for 10 s before injection, mean pain severity score was significantly lower (Öztürk et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside these, studies that suggest performing direct pressure to the injection site independent of acupressure points were also found to be effective for reducing injection pain (Derya et al, ; Nasiry et al, ; Öztürk et al, ). According to the study of Öztürk et al, after pressure was performed on the injection site for 10 s before injection, mean pain severity score was significantly lower (Öztürk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Beside these, studies that suggest performing direct pressure to the injection site independent of acupressure points were also found to be effective for reducing injection pain (Derya et al, ; Nasiry et al, ; Öztürk et al, ). According to the study of Öztürk et al, after pressure was performed on the injection site for 10 s before injection, mean pain severity score was significantly lower (Öztürk et al, ). As similar, in a study by Derya et al, it was determined that the mean pain severity score of the group for whom manual pressure was performed before injection was significantly lower than the control group (Derya et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnhill et al (), Chung et al () and Öztürk et al () compared a group with the application of manual pressure with a group without the application of manual pressure at the injection site (Figure ). Regarding the results of individual studies in the meta‐analysis, these studies reported that participants in the manual pressure groups reported lower pain intensity scores (at a small to moderate level) relative to those in the comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the level of pain during IM injections. Included among the studies that were used in this meta‐analysis, the study by Öztürk Baykara Karadag and Eyikara () examined the efficiency of manual pressure before IM injections in young adults. This study showed that the application of manual pressure to the injection site prior to the IM injection decreased the level of pain intensity.…”
Section: Introductionmentioning
confidence: 99%